KAJIAN ETIKA PENYUSUNAN LAPORAN KEUANGAN BERBASIS MAQASIDU SYARIAH - Rifqah Alfiyyah; Lince Bulutoding; Muslimin Kara (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to understand ethics in the preparation of financial statements and interpret the ethics of preparing financial statements based on maqashid sharia at the National Amil Zakat Agency (BAZNAS) Bone Regency. This research is a type of descriptive qualitative research using a phenomenological approach. Sources of data used in this study are primary data and secondary data. Primary data in the form of information and data obtained during observations and interviews in the research process. While secondary data is in the form of additional information or data obtained from trusted institutions or sources which have then been published to the general public for reprocessing in research. The results of this study indicate that with regard to the ethics of preparing financial statements carried out by BAZNAS, Bone Regency, it is in accordance with the existing rules in the implementation of financial statement disclosures which are also carried out every 6 months in accordance with Government Regulation of the Republic of Indonesia Number 14 of 2014 concerning the Implementation of Law No. Law Number 23 which regulates the Standard Operating Procedure (SOP). Then BAZNAS Bone Regency has also carried out its responsibilities in accordance with maqasidu sharia, namely by bridging the obligations of muzakki and mustahiq needs with a full sense of moral responsibility to Allah Subhanahu Wata'ala. Disclosure of financial reports carried out by BAZNAS Bone Regency has also covered several aspects such as physical, mental and spiritual aspects.